Traditional Sport "Sepit-Sepitan" in Bali Province - Fadlu Rachman; Taufik Hidayat Suharto; Ziko Fajar Ramadhan (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research aimed to study traditional sport sepit-sepitan in Bali Province qualitatively. The data used for this study was collected from observations, interviews, and document reviews. The methods that have been used in this study are observation, interview, and documentation. This research was conducted in Bali Province. The population of this study was made up of students who played traditional sports, local people, and local cultural figures. This study shows that the sepit-sepitan game was created by Made Taro who is a maestro of oral tradition arts from the Province of Bali who has dedicated himself for 42 years to spreading moral messages through fairy tales and traditional games. The Sepit-SepitanÂ game was inspired by the fairy tale about a wolf and a stork. The wolf was arrogant, always wanted to win alone, and did not want to be defeated, while the stork was skilled and flexible. The traditional sports media for the sepit-sepitan consists of a pincer, ball, guli, and bung-bung. The traditional sport of sepit-sepitan is a form of group sport consisting of four people in one group where each player has to put the ball and roll into the bung-bung according to the colour chosen. The fastest group that finishes throwing the ball and rolls into the bung-bung comes out as the winner.